TINJAUAN KEKUATAN PEMBUKTIAN DIGITAL SIGNATURE DALAM SENGKETA PERDATA YANG DITOLAK OLEH HAKIM SEBAGAI ALAT BUKTI DITINJAU DARI UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - NIM. A1011151146, LEO MARTUA (Fakultas Hukum Universitas Tanjungpura, 2022)
Abstrac In this thesis, the author raises the issue of Reviewing the Strength of Evidence of Digital Signature in Civil Disputes Rejected by Judges as Evidence Judging from Law Number 11 of 2008 concerning Information and Electronic Transactions. In the decision of the Supreme Court Number 372/Pdt.G/2015/PN.Jkt.Pst. in a lawsuit between PT. Transnusa Aviation Mandiri against Wakatobi PTE. LTD. there is evidence submitted in the form of electronic letters. In the decision it was explained that the proof of print out by the Plaintiff was seen as proof of the agreement, while the Government Regulation regarding electronic signatures did not exist and there was no proof of print outs either and the form of electronic signature had not yet been determined. If in a conventional written agreement the execution of